(untitled) (Academicia Globe: Inderscience Research, 2024)
The article examines the concept of intercultural competence of university students, provides the points of view of foreign and Russian scientists, and proposes pedagogical scenarios for the use of telecommunication technologies for the development of intercultural competence of students in the process of teaching foreign languages.